TEACHING MATHEMATICS TO STUDENTS WITH HEARING IMPAIRMENTS (Interdisciplinary Studies Journal, 2025)
The present article aims to analyze strategies that promote access for students with hearing impairments, enrolled in the final years of elementary school, to an inclusive and quality mathematics education. To this end, a qualitative, exploratory study was conducted, using a bibliographic approach complemented by direct observation carried out in a public school located in the municipality of Macapá, in the state of Amapá. The analysis of the collected data was conducted through the content analysis technique, in order to systematically interpret the information obtained during the investigative process. The results indicate that interpretation, specific vocabulary, body and visual expressions, and problem-solving in mathematics teaching appear to be effective strategies for mathematics teaching and learning, as experimentation, manipulation, and the construction of knowledge in a playful and interactive way contribute to the development of essential mathematical skills and to the formation of critical and autonomous citizens.
Keywords: Inclusive Education; Hearing Impairment; Mathematics Teaching; Elementary Education